First row transition metal complexes of a hexadentate pyrazole-based bispidine ligand - Comba, Peter; Morgen, Michael; Wadepohl, Hubert (Polyhedron, 2013)
The efficient synthesis of a new hexadentate pyrazole-based bispidine-ligandand its first-row transition metal complexes (FeII, CoII, NiII, CuII and ZnII) is reported. There are interesting structural differences between the present and earlier hexadentate bispidine ligands (tetragonally versus trigonally distorted octahedral geometries). The structural analysis of the metal-free ligand and the five complexes shows that the structure enforced by the rigid pyrazole-based bispidine is best described as distorted trigonal prismatic, and this also emerges from the spectroscopic analysis.